Advancing Professional Competence of Teachers via Classroom Action Research - Mami Hajaroh; Lusila Andriani; Wulan Tri Puji Utami; Ebni Sholikhah; Ayusti Nur Utami (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Teachers possess a central role in shaping the quality of education by improving professional competence through Classroom Action Research (CAR) training. CAR enables teachers to conduct practical research in the classroom, identifying problems and finding concrete solutions. Training not only improves the teaching skills but also enhances the quality of classroom learning. Therefore, this research aimed to build the capacity for professional competence among teachers at Indonesian School of Kota Kinabalu (SIKK). It also improved the insight and action research skills in the school and Community Learning Center (CLC) in Kota Kinabalu, Sabah, Malaysia. Training strategy was carried out through blended learning both online and offline. The online training used Zoom platform and Google Classroom Learning Management System, while the offline model was performed in Kota Kinabalu. The methods included dialogue, games, direct practice, and assignments. The results showed that teachers' satisfaction with training services was due to the usefulness of the materials, relevance to the needs, and effective communication during training. The understanding and skills in CAR were also found to be increasing. Additionally, teachers needed to make behavioral changes in classroom learning by conducting CAR. This research finally showed that CAR and the publication of the results would improve the achievement and quality of education. The professional competence and CAR were interrelated concepts where CAR functioned as a method to help teachers identify and overcome learning problems in the classroom systematically and scientifically. Furthermore, the professionalism referred to the abilities, skills, and ethics passed by educators to carry out educational roles effectively, and with dignity when CAR was performed.